Información financiera y su incidencia en la toma de decisiones en la Empresa Casa Plast E.I.R.L, 2019 – 2020 - Vela Caro, Luis Eduardo (2022)
At present, decision-making becomes a fundamental phase in the smooth running of any business, for this it is necessary that these have timely useful financial information which facilitates this process for the benefit of the organization, in the present study it was applied to a commercial company with a population of 20 collaborators immersed in management so that from their perception the Incidence of Financial Information in decision-making is identified, which will serve as a reference to understand this process in other companies of similar size, for For this, an investigation was implemented with a quantitative approach, of a cross-sectional descriptive type and a non experimental design, in which it was identified in a relevant way that the techniques of analysis of the financial statements affect an average of 65% almost always and always in the decision-making process. decisions related to investments, financing and operation of the company, which on average 64% of participate tes considers that financial information has an influence on the decision process, in the same way the majority of collaborators consider that for access to credits or to start new projects the financial information is reviewed almost always and always, that the company takes into account indicators of liquidity and profitability and that 40% would never make decisions without having complete and reliable information, so it is concluded that financial information has a positive impact on the company's decision making.